From Waste to Sustainable Pavements: Performance Evaluation of Eggshell and Green Mussel Shell Ash as Partial Cement Substitutes in Paving Blocks - Randy Setiawan; Deny Syarani; Ahmad Muhtadi; Janne Hillary (WISE Pendidikan Indonesia, 2026)
This study investigates the potential use of eggshell ash and green mussel shell ash as partial cement substitutes in the production of paving blocks intended for pedestrian pavement applications. The research aims to support sustainable construction practices by reducing cement consumption while maintaining adequate mechanical performance. An experimental method was adopted by incorporating the biowaste ashes into paving block mixtures at substitution levels of 2.5%, 5.0%, and 7.5% by weight of cement, with conventional paving blocks used as control specimens. Laboratory testing was conducted in accordance with Indonesian National Standards to evaluate aggregate physical properties, compressive strength at curing ages of 7 and 28 days, and water absorption behavior. The results show that paving blocks containing eggshell and green mussel shell ash achieved compressive strength values that met and, in some cases, exceeded the minimum requirement for pedestrian pavements. The optimum mixture was observed at a substitution level of approximately 5%, where the 28-day compressive strength surpassed the target design strength of 20 MPa, despite a minor reduction in early-age strength at 7 days. Water absorption values remained within acceptable limits, indicating that the inclusion of biowaste ash did not negatively affect durability-related performance. These findings highlight that calcium-rich biowaste materials can be effectively utilized as sustainable cement substitutes in non-structural paving applications. The study contributes to the advancement of circular economy strategies in the construction sector by promoting waste valorization, minimizing environmental impact, and offering an eco-friendly alternative for pedestrian infrastructure development.